2009
DOI: 10.1515/bc.2009.033
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione dysregulation and the etiology and progression of human diseases

Abstract: Glutathione (GSH) plays an important role in a multitude of cellular processes, including cell differentiation, proliferation, and apoptosis, and as a result, disturbances in GSH homeostasis are implicated in the etiology and/or progression of a number of human diseases, including cancer, diseases of aging, cystic fibrosis, and cardiovascular, inflammatory, immune, metabolic, and neurodegenerative diseases. Owing to the pleiotropic effects of GSH on cell functions, it has been quite difficult to define the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
703
0
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 948 publications
(728 citation statements)
references
References 302 publications
(386 reference statements)
12
703
0
13
Order By: Relevance
“…A fairly large number of studies have shown age-dependent decreases in total GSH and/or reduced GSH levels in the brain (for reviews see [3,25,53]). In addition, age-dependent increases in glutathione disulfide (GSSG), the oxidized form of GSH have been observed in both mouse [72] and rat [67] brains.…”
Section: Maintenance Of Gshmentioning
confidence: 99%
“…A fairly large number of studies have shown age-dependent decreases in total GSH and/or reduced GSH levels in the brain (for reviews see [3,25,53]). In addition, age-dependent increases in glutathione disulfide (GSSG), the oxidized form of GSH have been observed in both mouse [72] and rat [67] brains.…”
Section: Maintenance Of Gshmentioning
confidence: 99%
“…These observations together with this study lead to the hypothesis that the functional output of c-Fos induction by OHT may depend on whether or not there is a concomitant c-Jun activation by JNK signaling. As antioxidant pathways are often enhanced in cancer cells (Friesen et al, 2004;Young et al, 2004;Recktenwald et al, 2008;Ballatori et al, 2009), the resistance of certain cancer cells to tamoxifen may depend on their ability to prevent ROS accumulation and in turn JNKspecific activation of c-Jun. In line with this hypothesis we found that OHT induced ROS accumulation in SkBr3 cells but not in LNCaP cells (Figure 8).…”
Section: C-jun Mediates 4-hydroxytamoxifen-induced Apoptosismentioning
confidence: 99%
“…Low intracellular GSH levels would decrease the cellular antioxidant capacity. Several reports have suggested that a decrease in GSH levels is also associated with immune system dysfunction and inflammation in humans (Ballatori et al 2009;Ghezzi 2011). In the present study, the depletion of GSH and the elevation of GSSG could result in damage to the immune system, which would decrease the resistance to disease.…”
Section: Resultsmentioning
confidence: 52%